+0

# umwandlung in TE

0
851
1

RE=RA*[1+alpha*(TE-TA)] -> TE = ?

05.10.2015

### Beste Antwort

#1
+26379
+9

RE=RA*[1+alpha*(TE-TA)] -> TE = ?

$$\small{ \begin{array}{rcll} R_E &=& R_A\cdot [1+\alpha \cdot (T_E-T_A)] \qquad &| \qquad : R_A \\ \dfrac{R_E}{R_A} &=& 1+\alpha \cdot (T_E-T_A) \qquad &| \qquad -1\\ \dfrac{R_E}{R_A}-1 &=& \alpha \cdot (T_E-T_A) \qquad &| \qquad :\alpha\\ \left(\dfrac{R_E}{R_A}-1 \right)\cdot \left(\dfrac{1}{\alpha} \right) &=& T_E-T_A \qquad &| \qquad +T_A \\ T_A+\left(\dfrac{R_E}{R_A}-1 \right)\cdot \left(\dfrac{1}{\alpha} \right) &=& T_E \\ \mathbf{T_E} & \mathbf{=} & \mathbf{T_A+\left(\dfrac{R_E}{R_A}-1 \right)\cdot \left(\dfrac{1}{\alpha} \right)} \\ \mathbf{T_E} & \mathbf{=} & \mathbf{T_A+ \dfrac{R_E-R_A}{R_A\cdot \alpha} } \\ \end{array} }$$

05.10.2015

#1
+26379
+9
Beste Antwort

RE=RA*[1+alpha*(TE-TA)] -> TE = ?

$$\small{ \begin{array}{rcll} R_E &=& R_A\cdot [1+\alpha \cdot (T_E-T_A)] \qquad &| \qquad : R_A \\ \dfrac{R_E}{R_A} &=& 1+\alpha \cdot (T_E-T_A) \qquad &| \qquad -1\\ \dfrac{R_E}{R_A}-1 &=& \alpha \cdot (T_E-T_A) \qquad &| \qquad :\alpha\\ \left(\dfrac{R_E}{R_A}-1 \right)\cdot \left(\dfrac{1}{\alpha} \right) &=& T_E-T_A \qquad &| \qquad +T_A \\ T_A+\left(\dfrac{R_E}{R_A}-1 \right)\cdot \left(\dfrac{1}{\alpha} \right) &=& T_E \\ \mathbf{T_E} & \mathbf{=} & \mathbf{T_A+\left(\dfrac{R_E}{R_A}-1 \right)\cdot \left(\dfrac{1}{\alpha} \right)} \\ \mathbf{T_E} & \mathbf{=} & \mathbf{T_A+ \dfrac{R_E-R_A}{R_A\cdot \alpha} } \\ \end{array} }$$

heureka 05.10.2015